2018
DOI: 10.4143/crt.2017.552
|View full text |Cite
|
Sign up to set email alerts
|

Negative Conversion of Progesterone Receptor Status after Primary Systemic Therapy Is Associated with Poor Clinical Outcome in Patients with Breast Cancer

Abstract: PurposeAlteration of biomarker status after primary systemic therapy (PST) is occasionally found in breast cancer. This study was conducted to clarify the clinical implications of change of biomarker status in breast cancer patients treated with PST.Materials and MethodsThe pre-chemotherapeutic biopsy and post-chemotherapeutic resection specimens of 442 breast cancer patients who had residual disease after PST were included in this study. The association between changes of biomarker status after PST and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
2
19
1
2
Order By: Relevance
“…Previous studies on HER2 change after NAC are summarized in Table 4. In our study, HER2 status was altered after NAC in 3.4% with positive to negative conversion in 0.9% and negative to positive conversion in 2.5% [52]. Most cases with negative to positive conversion of HER2 status after NAC showed low level of HER2 amplification, and the HER2/CEP17 ratio ranged from 2.2 to 4.4 (data not shown in a previous study) [52].…”
Section: Changes In Her2 Status After Neoadjuvant Chemotherapysupporting
confidence: 46%
See 2 more Smart Citations
“…Previous studies on HER2 change after NAC are summarized in Table 4. In our study, HER2 status was altered after NAC in 3.4% with positive to negative conversion in 0.9% and negative to positive conversion in 2.5% [52]. Most cases with negative to positive conversion of HER2 status after NAC showed low level of HER2 amplification, and the HER2/CEP17 ratio ranged from 2.2 to 4.4 (data not shown in a previous study) [52].…”
Section: Changes In Her2 Status After Neoadjuvant Chemotherapysupporting
confidence: 46%
“…In our study, HER2 status was altered after NAC in 3.4% with positive to negative conversion in 0.9% and negative to positive conversion in 2.5% [52]. Most cases with negative to positive conversion of HER2 status after NAC showed low level of HER2 amplification, and the HER2/CEP17 ratio ranged from 2.2 to 4.4 (data not shown in a previous study) [52]. Cockburn et al [61] also reported the mean HER2/CEP17 ratio in resection specimens with HER2 positive conversion was 3.7.…”
Section: Changes In Her2 Status After Neoadjuvant Chemotherapymentioning
confidence: 50%
See 1 more Smart Citation
“…We found a statistically significant decrease in PR expression values between biopsy and surgical specimens after NAT, which is consistent with other reports where the PR, along with the Ki67 index, are the most commonly altered biomarkers after NAT administration [7,15,16,31]. Contrary to what has been reported for Ki67, PR expression loss has been associated with worse tumor characteristics [15] and poor clinical outcomes [23,32,40]. It has also been shown that loss of PR expression may be an indicator of a decrease of hormone sensitivity in tumor cells, activation of alternate proliferation pathways such as PI3K/AKT/mTOR [41,42], and also, the induction of a non-functional ER state which could lead to a diminished response to endocrine therapy, specifically in ERpositive/PR-negative tumors [18,43].…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, we aimed to analyze changes in IHC biomarker status and expression in paired biopsy and surgical samples in breast cancer cases treated and non-treated with NAT, given that changes in biomarker expression may have several clinical implications for disease outcome in breast cancer patients [31][32][33]. It may also affect adjuvant therapy regimen, as variation in breast cancer intrinsic subtype after NAT could lead to the addition or discontinuation of therapy schemes [16,34].…”
Section: Discussionmentioning
confidence: 99%